PESAN DAKWAH DALAM KEBIJAKAN PARIWISATA HALAL PADA PEMERINTAH PROVINSI NUSA TENGGARA BARAT - Wirawan, Agung (KOMUNIKE, 2021)
Tourism is a growing and increasingly specific industry. one of which is halal tourism. NTB as a province that won world awards through halal tourism, makes policies in the form of regional regulations as guidelines for implementing halal tourism. Aside from being an implementation guide, the policy is a da'wah containing material or messages of Islamic da'wah. This research is a field research with a qualitative approach, with descriptive data presentation. Article by article in the regional regulation on halal tourism reflects an invitation, as well as motivates the goodness and safety of the hereafter. This is in line with the notion of da'wah which in terms is an attempt to invite others to embrace Islam, practice the creed and shari'ah. In conclusion, the implementation of halal tourism continues to be optimized by local governments. Although the message of da'wah in halal tourism policies contains messages of faith, muamalah, sharia and morals, the community as tourism actors carry out many halal tours because of their habits and characteristics, the majority of whom are Muslims.